Collected essays of harvey leibenstein (Vol.2) - Button, Kenneth (ed.) (New York, 1989)
This major new book presents in two volumes Professor Leibenstein's seminal contributions to economic theory and application. Volume 1 focuses on Leibenstein's work in the fields of population, development and welfare and, in particular, highlights his contributions to fertility theory, economic growth and technical progress. The selection has been made from over 100 academic papers and nine books written during the last 40 years. It represents the diversity of Professor Leibenstein's interest and the originality of his thinking.
Keywords: Micro economics